Activated Sugar Precursors: Biosynthetic Pathways and Biological Roles of an Important Class of Intermediate Metabolites in Bacteria - Sousa, Sílvia A.; Feliciano, Joana R.; Leitao, Jorge H. (IntechOpen, 2011)
None